Early postoperative loss of disc height following transforaminal and lateral lumbar interbody fusion: a radiographic analysis - Kaliya-Perumal, Arun-Kumar (2022)
Study Design: Retrospective comparative radiological study. Purpose: To analyze the difference in early disc height loss following transforaminal and lateral lumbar interbody fusion (TLIF and LLIF). Overview of Literature: Minimal disc height loss facilitated by the polyaxial screw heads can occur naturally due to mechanical loading following lumbar fusion procedures. This loss does not usually cause any significant foraminal narrowing. However, when there is concomitant cage subsidence, symptomatic foraminal compromise could occur, especially when posterior decompression is not performed. It is not known whether the type of procedure, TLIF or LLIF, could influence this phenomenon. Methods: Retrospectively, patients who underwent TLIF and LLIF for various degenerative conditions were shortlisted. Each of their fused levels with the cage in situ was analyzed independently, and the preoperative, postoperative, and follow-up disc height measurements were compared between the groups. In addition, the total disc height loss since surgery was calculated at final follow-up and was compared between the groups. Results: Forty-six patients (age, 64.1±8.9 years) with 70 cage levels, 35 in each group, were selected. Age, sex, construct length, preoperative disc height, cage height, and immediate postoperative disc height were similar between the groups. By 3 months, disc height of the TLIF group was significantly less and continued to decrease over time, unlike in the LLIF group. By 1 year, the TLIF group demonstrated greater disc height loss (2.30±1.3 mm) than the LLIF group (0.89±1.1 mm). However, none of the patients in either group had any symptomatic complications throughout follow-up. Conclusions: Although our study highlights the biomechanical advantage of LLIF over TLIF in maintaining disc height, none of the patients in our cohort had symptomatic complications or implant-related failures. Hence, TLIF, as it incorporates posterior decompression, remains a safe and reliable technique despite the potential for greater disc height loss.